Astonishing diversity—the medicinal plant markets of Bogotá, Colombia - Bussmann, Rainer W.; Paniagua Zambrana, Narel Y.; Romero, Carolina; Hart, Robbie E. (Journal of ethnobiology and ethnomedicine, 2018)
Despite the importance of local markets as a source of medicinal plants in Colombia, comparatively little comparative research reports on the pharmacopoeiae sold. This stands in contrast to wealth of available information for other components of plant use in Colombia and other countries. The present provides a detailed inventory of the medicinal plant markets in the Bogotá metropolitan area, hypothesizing that the species composition, and medicinal applications, would differ across markets of the city. From December 2014 to February 2016, semi-structured interviews were conducted with 38 plant vendors in 24 markets in Bogotá in order to elucidate more details on plant usage and provenance. In this study, we encountered 409 plant species belonging to 319 genera and 122 families. These were used for a total of 19 disease categories with 318 different applications. Both species composition and uses of species did show considerable differences across the metropolitan area-much higher in fact than we expected. The present study indicated a very large species and use diversity of medicinal plants in the markets of Bogotá, with profound differences even between markets in close proximity. This might be explained by the great differences in the origin of populations in Bogotá, the floristic diversity in their regions of origin, and their very distinct plant use knowledge and preferences that are transferred to the markets through customer demand. Our study clearly indicated that studies in single markets cannot give an in-depth overview on the plant supply and use in large metropolitan areas.